Synergistic gene expression during the acute phase response is characterized by transcription factor assisted loading - Goldstein, Ido (Nat Commun, 2017)
The cytokines interleukin 1β and 6 (IL-1β, IL-6) mediate the acute phase response (APR). In liver, they regulate the secretion of acute phase proteins. Using RNA-seq in primary hepatocytes, we show that these cytokines regulate transcription in a bifurcated manner, leading to both synergistic and antagonistic gene expression. By mapping changes in enhancer landscape and transcription factor occupancy (using ChIP-seq), we show that synergistic gene induction is achieved by assisted loading of STAT3 on chromatin by NF-κB. With IL-6 treatment alone, STAT3 does not efficiently bind 20% of its coordinated binding sites. In the presence of IL-1β, NF-κB is activated, binds a subset of enhancers and primes their activity, as evidenced by increasing H3K27ac. This facilitates STAT3 binding and synergistic gene expression. Our findings reveal an enhancer-specific crosstalk whereby NF-κB enables STAT3 binding at some enhancers while perturbing it at others. This model reconciles seemingly contradictory reports of NF-κB-STAT3 crosstalk.